Geometry effect on post-dryout heat transfer. - Zhang, Ji. (University of Ottawa (Canada), 1998)
A thorough literature review of the effects of channel shape and spacing devices on post-dryout heat transfer has been performed. Overall, very little information is available for these effects, several experiments were carried out covering only limited flow conditions and geometries. To extend the present review, studies with air flow through heated channels have also been included. The effect of channel shape is small for channels with rounded corners, but is rather significant for those with sharp corners (especially those of small apex angle). As a result, the heat transfer rate is much lower in a triangular than a rectangular channel at the same flow conditions (the heat transfer rate in tubes is often the highest). In addition, the circumferential heat flux distribution affects the overall heat transfer rate considerably (e.g., comparing triangular channels with either one-side or all-side heated). A strong effect of spacing devices on heat transfer has been observed in both single-phase and post-dryout studies. It enhances significantly the heat transfer rate at locations downstream of the spacer. Most studies showed an exponentially decaying trend of heat transfer enhancement with increasing distance away from the spacer. Correlations have been proposed to represent this trend; they can only be applied to specific range of flow conditions due to the limited database. In view of the deficiency among existing prediction methods, correlations for the effects of channel shape and spacing devices on post-dryout heat transfer have been developed to improve the prediction accuracy and range of applications. These correlations provide good agreement with experimental data obtained in other studies. Furthermore, they exhibit correct asymptotic and parametric trends and hence can be extrapolated to conditions beyond the present database. However, it is difficult to quantify the uncertainty of the extrapolation due to a lack of data.
Keywords: Engineering, Mechanical.